2016
DOI: 10.1111/tsq.12113
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Emotional Labor at Worker-Owned Businesses: Deep Acting, Surface Acting, and Genuine Emotions

Abstract: Members of worker cooperatives—organizations collectively owned and democratically run by their workers—report substantial differences in how they can or must perform various emotions, compared with previous work at conventional, hierarchical organizations. First, some emotions not allowed in conventional workplaces are fully permitted at worker cooperatives, including negative emotions, like anger, but also positive emotions, like enthusiasm. In contrast, other emotions must be displayed, even if insincere. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Research has found that the rhetoric of "efficiency" can impede cooperative values such as egalitarianism (Taylor, 1994). Others have studied the challenges associated with not anticipating diversity and inequality (Meyers & Vallas, 2016) and the emotional work necessary for cooperation (Hoffmann, 2016). Comparing a bakery and a grocery cooperative, Meyers and Vallas (2016) show how the implementation of a "utilitarian" versus a "communitarian" regime resulted in stratifying types of participation along race, class, and gender lines.…”
Section: Cooperation In Cooperativesmentioning
confidence: 99%
“…Research has found that the rhetoric of "efficiency" can impede cooperative values such as egalitarianism (Taylor, 1994). Others have studied the challenges associated with not anticipating diversity and inequality (Meyers & Vallas, 2016) and the emotional work necessary for cooperation (Hoffmann, 2016). Comparing a bakery and a grocery cooperative, Meyers and Vallas (2016) show how the implementation of a "utilitarian" versus a "communitarian" regime resulted in stratifying types of participation along race, class, and gender lines.…”
Section: Cooperation In Cooperativesmentioning
confidence: 99%
“…Sociologist Hoffmann () takes up this important set of questions in her article in this section. Her work is grounded in her multiyear field study of four workers’ co‐operatives in four different industries.…”
Section: Challenges To Co‐operative/democratic Organizationsmentioning
confidence: 99%
“…Some workers’ co‐operatives are discovering ways to combat gender inequities, such as the workers’ recovered firm studied by Sobering (). And, some of the co‐operatives and civil society groups are learning how to infuse authentic emotions into their public conversations (Hoffmann ). Democratic control of enterprises by their members (and ownership where there is something to own) opens up a whole new logic of organization to people and pushes members to practice a new vocabulary of motives and emotions, new decisional practices, and new relations with each other.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Hochschild defines emotional labor as an attempt to regulate facial expressions and body movements (gestures and mimics) that can be observed by others in the society in which they are found. The author argued that emotional labor is part of the labor force, such as physical and mental labor [9]. Hochschild defines emotional labor as the facial and body manifestation of emotions that can be analyzed.…”
Section: Emotional Labormentioning
confidence: 99%
“…It has been shown as a reson for this, the employee who is under the influence of negative emotions is more cautious and detailed in his work, at the same time he is more cautious towards the customer [10]. In contrast, it is emphasized the importance of positive feelings by Hoffman's [9] study and positive emotions have expanded the creativity of how the individual behaves but negative emotions can limit this [9]. According to the results of the research done by Tepeci [19] showed that that the job satisfaction of individuals who exhibit profound behavior is increasing whereas those job satisfaction who display superficial behaviors have decreased [12].…”
Section: Introductionmentioning
confidence: 99%